Millimeter-wave beam scattering and induced broadening by plasma turbulence in the TCV tokamak. (29th April 2021) - Chellaï, O.; Alberti, S.; Furno, I.; Goodman, T.; Maj, O.; Merlo, G.; Poli, E.; Ricci, P.; Riva, F.; Weber, H.
Abstract: The scattering of millimeter-wave beams from electron density fluctuations and the associated beam broadening are experimentally demonstrated. Using a dedicated setup, instantaneous deflection and (de-)focusing of the beam due to density blobs on the beam path are shown to agree with full-wave simulations. The detected time-averaged wave power transmitted through the turbulent plasma is reproduced by the radiative-transfer model implemented in the WKBeam code, which predicts a ∼50% turbulence-induced broadening of the beam cross-section. The role of core turbulence for the considered geometry is highlighted.